1991
DOI: 10.1063/1.104970
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic integration of a resonant tunneling diode and a quantum well semiconductor laser

Abstract: Negative transconductance resonant tunneling field effect transistors and monolithically integrated resonant tunneling diodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The intrinsic bistability-where charge storage allows two different states of band bending for one applied bias-has been observed by Alves et al [21] and explained theoretically in [22] and [23]. The extrinsic bistability is illustrated in the load line analysis of [10] and is caused by the presence of the laser diode and series resistance.…”
Section: Monolithically Integrated Rtd-ldmentioning
confidence: 92%
See 2 more Smart Citations
“…The intrinsic bistability-where charge storage allows two different states of band bending for one applied bias-has been observed by Alves et al [21] and explained theoretically in [22] and [23]. The extrinsic bistability is illustrated in the load line analysis of [10] and is caused by the presence of the laser diode and series resistance.…”
Section: Monolithically Integrated Rtd-ldmentioning
confidence: 92%
“…To visualise why the RTD-LD module exhibits electrical and optical bistability with the presence of series resistance it is worth while considering the graphical technique of load line analysis described in detail in [10]. The reason for the high extinction ratio observed is due to fact that the threshold current of the laser diode of 24 mA lies between the peak and valley currents of the laser ( ) such that the laser switches fully "on" or "off" at the and switching points.…”
Section: Rtd-ld Modulementioning
confidence: 99%
See 1 more Smart Citation
“…The TJ requires materials with high n-type and p-type doping levels, low dopant diffusion, and large and gaps to avoid absorption. Third, the forward-biased tunnel junction with a high doped ntype and p-type layers are located on the top of LD [4], [5], the negative differential resistance (NDR) of the TJ have been used in optical bistable devices, which are the key components in future optical switching and computing systems. The principle of these devices is the tunnel diode section provides a differential negative resistance which induces an electrically bistable characteristic when connected in series with the laser section and an external load.…”
Section: Introductionmentioning
confidence: 99%
“…Grave et al [5] have demonstrated an integrated RTD/laser in the GaAs-AlGaAs material system and have demonstrated its application as an optical two state memory. In this work, we are targeting optical communications applications with the emphasis on increased functionality and an emission wavelength of around 1.55 m. We have characterized the low-frequency operation of the RTD-LD, demonstrated optical/electrical bistability, and modeled its electrical characteristics using SPICE [6].…”
mentioning
confidence: 99%